Longford, Clay County - Todd, Lauren (Kansas State University, The Chapman Center for Rural Studies, 2013)
This is a study of the currently viable small town of Longford, Kansas, in Clay County. It traces the history of the town from its founding as a railroad community on the ATSF line heading west through its survival today. Sources include interviews with current residents and a town historian as well as maps, early photographs, and site visits.
Lauren Todd, “Longford, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/120.
Keywords: Chapman Township; Clay County; Evangelical Brethren Church; Longsford; William McKale; Saline Cement and Plaster Company